The multinational banking industry - Coulbeck, Neil, 1952- (Routledge library editions. Banking and finance, 2012)
The role of international banks within the developed economies has come under increasingly hostile public scrutiny, yet little attention has been paid to the structure and purpose of the banks themselves. Most existing studies concentrate on the part played by international banks as intermediaries in the domestic and international economy, failing to consider the foremost concern of the banks themselves - their success as business enterprises. This book examines the practical problems faced by the Universal Multinational banks (UMNBs) in the fields of strategic planning and business developmen.